Uji Pengaruh Pendapatan dan Biaya Operasional terhadap Kinerja Keuangan : (Studi Kasus Subsektor Hotel, Restoran, dan Pariwisata di BEI) - Leya Safitri; Artie Arditha Rachman; M Muhayin A Sidik (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted to determine the effect of revenues and operational costs on the financial performance of hotel, restaurant and tourism subsector companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023. This research uses 2 independent variables in the form of revenues and operational costs. The dependent variable is financial performance measured using the return on asset ratio. The population in this research is 50 companies in the hotel, restaurant and tourism subsector registered on the IDX in 2019-2023. Sampling used purposive sampling technique. The total research sample was 16 companies with 80 financial report data tested using multiple linear regression analysis. The results of the research that has been carried out show simultaneously revenues and operational costs have an effect on financial performance.